The evolution of armed non-state actors: The case of Iraq - Samra, Ahmed (AUC Knowledge Fountain, 2016)
This paper will seek to analyze and gauge to what extent have armed Non-State Actors evolved in the current international system, as well as how these groups have developed their power and ambition to rival and challenge the states they exist within and also influence other states around them. Using the classical Realist definitions for power and actors in international relations an analysis will be conducted to understand the whether states have a monopoly on power in the current international system. From a classical Realist perspective disagreements within the state are corrected when policy is being developed to reflect a united vision for the state’s interests. Several changes that will be discussed further in this paper have empowered and given agency to Armed Non-State Actors to not only challenge the states that they exist within but develop relations or challenge other states in the international system.